2021
DOI: 10.1038/s41419-021-04463-4
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of miR-24-3p promotes epithelial cell apoptosis and impairs the recovery from intestinal inflammation

Abstract: While apoptosis plays a significant role in intestinal homeostasis, it can also be pathogenic if overactive during recovery from inflammation. We recently reported that microRNA-24-3p (miR-24-3p) is elevated in the colonic epithelium of ulcerative colitis patients during active inflammation, and that it reduced apoptosis in vitro. However, its function during intestinal restitution following inflammation had not been examined. In this study, we tested the influence of miR-24-3p on mucosal repair by studying re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Loss of miR-24-3p promotes epithelial cell apoptosis and impairs the recovery from intestinal inflammation. 38 MiR-200b-3p alleviates TNF-α-induced apoptosis and inflammation of intestinal epithelial cells and ulcerative colitis progression in rats. 39 Here, we identified that miR-222-3p has a binding site for SOCS1 by bioinformatics analysis and confirmed their targeted relationship.…”
Section: Discussionmentioning
confidence: 98%
“…Loss of miR-24-3p promotes epithelial cell apoptosis and impairs the recovery from intestinal inflammation. 38 MiR-200b-3p alleviates TNF-α-induced apoptosis and inflammation of intestinal epithelial cells and ulcerative colitis progression in rats. 39 Here, we identified that miR-222-3p has a binding site for SOCS1 by bioinformatics analysis and confirmed their targeted relationship.…”
Section: Discussionmentioning
confidence: 98%
“…The dysregulation of MIR4435-2HG in UC might play a key role in the inflammatory process and has been shown to be associated with CRC [ 37 , 42 , 43 ]. MIR4435-2HG is correlated with the expression of B cell lymphoma 2 (Bcl-2)-interacting protein (BCL2L11), which is associated with an increase in apoptosis resistance, resulting in impaired epithelial cell turnover [ 44 ]. In addition, BCL2L11 also plays a major role in immune tolerance in UC [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To explore the anti-inflammatory effect of ATR on RAW264.7 cells, alterations in TNF-α, IL-6, SOD, MDA, and GSH were examined using ELISA, and ROS were examined using flow cytometry. The results depicted in Figure 2A,B demonstrate that ATR at various concentrations (1,5,25, and 125 μg/mL) significantly inhibited the secretion of TNF-α in LPS-induced RAW264.7 inflammatory cells (p < 0.05). However, only a high dosage (125 g/mL) of ATR was able to suppress the proinflammatory cytokine IL-6 in a doseindependent manner.…”
Section: Atr Inhibits Lps-induced Inflammatory Reactions In Raw2647 C...mentioning
confidence: 90%
“…Ulcerative colitis (UC) is a chronic inflammatory disease of the colon and rectum [1], characterized by a course of relapsing and remitting symptoms. The defining features of UC encompass bloody diarrhea, along with the occurrence of rectal urgency and tenesmus [2].…”
Section: Introductionmentioning
confidence: 99%